NYCTEREUTES MEGAMASTOIDES (CANIDAE, MAMMALIA) FROM THE EARLY AND MIDDLE VILLAFRANCHIAN (LATE PLIOCENE AND EARLY PLEISTOCENE) OF THE LOWER VALDARNO (FIRENZE AND PISA, TUSCANY, ITALY) - SAVERIO BARTOLINI LUCENTI (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
Among living canids, the genus Nyctereutes Temminck, 1838 was the first to appear in the Western European fossil record. In the Italian Peninsula, scanty remains from a few Plio-Pleistocene localities of central Italy, referable to the Triversa Faunal Unit (FU) and the Montopoli FU, were historically attributed to Nyctereutes megamastoides (Pomel, 1842). Here we describe the partially unpublished Nyctereutes remains from two localities of the Lower Valdarno (Tuscany), S. Giusto (Florence; early Villafranchian) and Montopoli (Pisa; middle Villafranchian), and compare them with both extant and fossil species of this genus. The material described herein most closely resembles the remains from Spain, France and other European sites previously attributed to N. megamastoides in proportions and morphological features, hence confirming the presence of this relatively widespread species in Italy from the Pliocene to the Early Pleistocene. Besides the scanty material, the Lower Valdarno record of N. megamastoides represents one of the earliest of the species in Europe and allows to report, for the first time, the occurrence of a derived form of Nyctereutes in the Late Pliocene of Italy. This early record confirms that the evolutionary pattern of Asia, where the advanced N. sinensis is associated with the primitive N. tingi, was different in the Pliocene of Europe.